Evaluation of Factors Associated with Malaria Infection Among Children Under-5 Years Who Received SMC - Muslim Adamu , Abdullahi Sabo Muhammad Yahaya Saleh (Sokoto Journal of Medical Laboratory Science)
Malaria is a major public health problem in Nigeria where it accounts for more cases and deaths than any other country in the world. Malaria is a risk for 97% of Nigeria's population. The remaining 3% of the population live in the malaria-free highlands. There are an estimated 100 million malaria cases with over 300,000 deaths per year in Nigeria. The aim of this study was to evaluate factors associated with malaria infection among children under-5 years who received SMC. This study was carried out as descriptive-analytical study. Inclusion criteria were strictly based on those children less than 5 years that were eligible for SMC. All those children above 5 years of age were excluded from the study. Few children were noted to come up with malaria fever despite taking the SMC medication which might be due to poor adherence to day 2 and day 3 medication (AQ), not combining SMC programme with other preventive measures against malaria such as the use of LLIN, fumigation and good environmental management. The most alarming was that some of the children coming up with malaria have been participating in the SMC programme for 2 or 3 years, and this might likely be due to the pfmdrl 86Y mutation which is associated with the AQ resistance which is very rare. Seasonal malaria chemoprevention is an intervention with great potential in Sokoto state, and along with other interventions. It could significantly contribute to approaching the threshold where elimination strategies will be envisioned. During the mass drug administration in all 23 LGAs, comprising 244 wards and 8269 settlements, the intervention significantly reduced hospital visit, admission, and malaria indicators among children.